2022
DOI: 10.1109/thms.2021.3128892
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Human Whole-Body Joint Torques During Overhead Work With a Passive Exoskeleton

Abstract: Overhead work is classified as one of the major risk factors for the onset of shoulder work-related musculoskeletal disorders and muscle fatigue. Upper-limb exoskeletons can be used to assist workers during the execution of industrial overhead tasks to prevent such disorders. Twelve novice participants have been equipped with inertial and force/torque sensors to simultaneously estimate the whole-body kinematics and the joint torques (i.e., internal articular stress) by means of a probabilistic estimator, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Active exoskeletons are promising devices for multiple health and occupational applications and their potential benefits have been examined through numerous studies since the first models of exoskeletons were developed in the late 1960s. In particular, their potential benefits in terms of preventing musculoskeletal disorders [1], [2], [3], [4] and fatigue [5], [6] have been thoroughly investigated in the recent literature. However, exoskeletons are still significantly altering human motor control and these potential benefits are not yet fully achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Active exoskeletons are promising devices for multiple health and occupational applications and their potential benefits have been examined through numerous studies since the first models of exoskeletons were developed in the late 1960s. In particular, their potential benefits in terms of preventing musculoskeletal disorders [1], [2], [3], [4] and fatigue [5], [6] have been thoroughly investigated in the recent literature. However, exoskeletons are still significantly altering human motor control and these potential benefits are not yet fully achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The following simplifications were made in this study: SC is a rotary joint 47 , 60 with two DOFs rotating around the X - and Y -axes (the basal joint of the entire upper limb and serves as a mechanical support). GH is a ball joint 47 , 61 , 62 with three DOFs rotating around the X -, Y - , and Z -axes (the largest range of motion joint in the upper limb and greatly extending upper limb motion). EL is a rotary joint 47 , 62 with one DOF rotating around the Z -axes (the composite joint structure contributes significantly to the stability of forearm motion).…”
Section: Resultsmentioning
confidence: 99%
“… GH is a ball joint 47 , 61 , 62 with three DOFs rotating around the X -, Y - , and Z -axes (the largest range of motion joint in the upper limb and greatly extending upper limb motion). EL is a rotary joint 47 , 62 with one DOF rotating around the Z -axes (the composite joint structure contributes significantly to the stability of forearm motion). WR is a rotary joint 47 , 63 with two DOFs rotating around the X - and Z -axes (the composite joint structure contributes significantly to the sophisticated motions and stability of the palm).…”
Section: Resultsmentioning
confidence: 99%
“…Another group of studies identified ergonomic interventions, such as new ergonomic workstations [ 243 ], tools [ 229 ] or training programs [ 239 ] that could be implemented in order to improve the working postures and reduce FSE. Other studies proposed exoskeletons or supporting devices in order to reduce the FSE, especially in prolonged posture maintenance and overhead working tasks [ 259 , 263 ] that require high loads on the neck, back and shoulder [ 261 ]. Another category included papers that design and validate alternative methods for assessing FSE during working activities, such as marker-less systems [ 286 , 306 ] or EMG measures [ 293 ].…”
Section: Discussionmentioning
confidence: 99%